Large-scale production and physicochemical characterization of human immune interferon. - Langford, M P (1979)
Large-scale production of crude high-titered (10(2.3) to 10(4) U/ml) human immune interferon (type II) was carried out in roller bottle cultures of human peripheral lymphocytes by using the T-cell mitogen staphylococcal enterotoxin A. Over 99% of human immune interferon was destroyed by pH 2 or heat at 56 degrees C for 1 h. The interferon was not neutralized by antibody to human leukocyte interferon. The kinetics of development of the antiviral state were slow for immune interferon relative to those for leukocyte interferon. Ultrogel AcA 54 chromatography of crude or the concentrated interferon resulted in two peaks of activity, a major one (87% of recovered activity) with a molecular weight of 40,000 to 46,000 and a minor peak of molecular weight 65,000 to 70,000. The column elution buffer consisting of 18% ethylene glycol and 1 M NaCl in phosphate-buffered saline resulted in at least 100% recovery of added interferon. The data suggest, then, that the interferon produced under large-scale conditions was immune (type II). The efficiency of the production was comparable to that described for large-scale production of human leukocyte interferon. Our large-scale production system for human immune interferon offers a feasible approach to preparation of large quantities of purified immune interferon for structure studies, antibody production, and clinical application.